Figurações da crueldade do Coringa nos quadrinhos de Batman: a piada mortal - Yida, Valéria (2016)
This research analyzes the Joker’s figurations of cruelty in the comic book Batman: A Piada Mortal (Batman: The Killing Joke, 1988). The cruelty of this character, understood as the wish to cause pain and suffering to another, has his own style in his lewd speech, in the following of an aesthetic of horror by the image-synthesis of his red rictus shaped mouth, as well as a plot that stages rituals of exhibitionism and sadism, in which the Joker's victims are offered in honor to Batman. This research contributes to the study of the villain in superhero genre comics, a character who, among clashes and truces with the hero, creates a field of tension that moves a suspenseful narrative of action and twists with an appeasing ending that invites the reader to the next adventure of the series. Cruelty is the Joker’s passion that wants to destabilize and corrupt the hero, composing the dynamics of a dense, ambiguous and sinister relationship between Batman and him. The aim of this research lies in this: what makes the Joker’s cruelty so outstanding in his relationship with Batman? By which means this cruelty determines and qualifies the Joker criminal acts, modifying his bound with the hero over the comics? The goal is to delimit the Joker’s imponderable of cruelty through its figurations that make him the quintessential villain in Batman stories. A two-way theoretical foundation was used: the via governed by image, professed by Thierry Groensteen, examining the complex system of narrative in which the drawing and the words are networked, and the psychoanalytical via in the Lacan’s trait unaire and perversion concepts, with the support of the Joker character’s approach to the literary figure of the sadean libertine